Neutralization of pertussis toxin by a single antibody prevents clinical pertussis in neonatal baboons - Nguyen, Annalee W. (Sci Adv, 2020)
Pertussis continues to cause considerable infant mortality world-wide, which could be addressed in part by passive immunization strategies. Antibody hu1B7 is a candidate therapeutic that potently neutralizes pertussis toxin in vitro, prevents leukocytosis in mice and treats established disease in weanling baboons as part of an antibody cocktail. Here, we evaluated the potential for hu1B7 and an extended half-life hu1B7 variant to prevent death, leukocytosis and other clinical symptoms in a newborn baboon model that mimics many aspects of human disease. We administered a single antibody dose to newborn baboons five weeks prior to experimental infection. While all animals were heavily colonized with Bordetella pertussis, prophylaxed animals showed significantly greater survival (P < 0.005), delayed and suppressed leukocytosis (P < 0.01) and enhanced clinical outcomes, including coughing (P < 0.01), as compared to controls. Together, this work demonstrates that a single neutralizing anti-PTx antibody is sufficient to prevent clinical pertussis symptoms.